The Influence of Internal Control Systems on the Implementation of Good Corporate Governance in Rural Banks in Pekanbaru - Al Amin, Roy (Riau International Conference on Economics, Business and Accounting, 2025)
The purpose of this study is to examine the influence of the Internal Control System on the implementation of Good Corporate Governance in Rural Banks (BPR) in Pekanbaru. The population in this study consists of Rural Banks (BPR) in Pekanbaru City. Respondents include directors, managers/heads of internal control systems, and managers/heads of accounting in each bank, with a total of 48 respondents completing the questionnaire. This study employs a census method. The data quality tests used include validity, reliability, and normality tests. Regression analysis is utilized to test the effect of the Internal Control System on the implementation of Good Corporate Governance. The results indicate that the Internal Control System has a significant effect on the implementation of Good Corporate Governance in Rural Banks in Pekanbaru, accounting for 53.90% of the variance, while the remaining 46.10% is determined by factors outside this research model.